PERBAIKAN PENAMPILAN TANAMAN KRISAN DENGAN INDUKSI MUTASI - Yusniwati PK. Dewi Hayati .; PK. Dewi Hayati (Jurnal Agroekoteknologi, 2009)
ABSTRACTResearch about the effect of multiple doses of gamma irradiation to improved the appearance of the chrysanthemum plant has been carried out on chrysanthemum varieties Gold van Langen-doses of gamma irradiation: 0 Gy, 5 Gy, 10 Gy, and 15 Gy.  Gamma irradiation has given at 2-week-old seedlings, which already have roots. Seeds that have been irradiated maintained up to 16 WAP. The results showed there are no all doses causes death in up to 16 WAP chrysanthemum seedlings but with a dose of 15 Gy seedlings did not grow at all. Dose of 5 Gy encourage the formation of lateral shoots on chrysanthemum. The higher the dose given causing the growth of seedlings of chrysanthemum hampered.Keywords:  Chrysanthemum, Mutation Induction, irradiation.